Developing Model of Colorectal Cancer Screening in Krathumbaen Community Network, Krathumbaen District, Samutsakorn Province - Wiriyakosol, Sukanya; Chaiteerakit, Roongkij; Lebkhao, Piya (Journal of Health Science of Thailand, 2019)
This descriptive study aimed to develop an operational approach for screening colorectal cancers with the participation of the health alliance, Krathumbaen district, Samutsakhon province in order that all groups of risky people lives in this area were able to participate in the screening project with the highest ratio of participation in fecal occult blood test and the colonoscopy, as well as the increasng ratio of the first-stage cancer finding. In screening stage, the team operators relied on the proactive operation to access all groups of people. It was performed by assigning officials of local district health offices to assess family history of colorectal cancer of people, to monitor the occult blood test by the village health volunteers who were responsible in each area, to screen and take the monks for the diagnosis at the hospital, and to send disseminate screening notifications to the government officers, teachers, and police respectively. Other activities included the screening of the average risk group in the industrial factories, the setting up of the special clinic for the screening of the colon and rectal cancers separate from the general surgery out patients clinic, setting-up of the fast track for patients to meet the surgeons and the anesthesiologists to make appointment for colonoscopy within 14 days after meeting the doctors; and schedulng colonoscopy on Saturday to facilitate those who were inconvenient to participate on the working days, particularly the government officials and their families. This study was carried out from January 2016 to April 2017. Data analysis was conducted through the use of descriptive statistics. It was found that there were 2,753 people with average risk and high risk participating in the screening program. Among them, 2,731 (98.2%) were screened with immunochemical fecal occult blood test (iFOBT). Altogether 597 people from the average risk group with positive occult blood test and high risk group with negative occult blood test were examined through the colonoscopy; and abnormal results were indentified in 242 cases (40.5%). There were 100 cases with adenomateous polyp (41.3%). Among the patients with abnormal results, 45 cases (18.5%) were found to have cancer: 31 cases (68.9%) with early stage cancer which increased from 42.86% observed in 2015; and 14 cases were found to have cancer at Stage 3 and 4 (31.1%, which decreases from 57.1% when compared with that in 2015).